2004
DOI: 10.1161/01.str.0000135761.18954.0b
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Stroke and Stroke Subtypes in Malmö, Sweden, 1990–2000

Abstract: Background and Purpose— The proportion of immigrants has increased in Sweden markedly during the last decades, as in many other Western countries. Incidence of stroke has increased during this period. However, it is primarily unknown whether incidence of stroke and stroke subtypes in Sweden is related to country of birth. Methods— Incidence of first-ever stroke was followed during 10 years in a cohort consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…Previous studies have demonstrated that immigrants to Sweden have an increased incidence of CVD [16,17]. However, we can only speculate whether the increased risk of hospitalizations due to HF among immigrants in the present study was related to a reduced or normal ejection fraction.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Previous studies have demonstrated that immigrants to Sweden have an increased incidence of CVD [16,17]. However, we can only speculate whether the increased risk of hospitalizations due to HF among immigrants in the present study was related to a reduced or normal ejection fraction.…”
Section: Discussioncontrasting
confidence: 56%
“…It has repeatedly been shown that immigrants in Sweden have higher risk of coronary heart disease and stroke compared to Swedish-born subjects [14-17]. In a previous study of the entire population of Malmö, Sweden, we found substantial differences in risk of HF hospitalization among foreign-born subjects [18].…”
Section: Introductionmentioning
confidence: 64%
“…However, studies have had divagating findings regarding the influence of SES on the incidence of CVD according to country of birth. One study reported that the increased incidence of myocardial infarction among foreign-born individuals was not influenced by socio-economic differences [9], while other studies have reported some or little effect of SES in relation to the incidence of stroke, CVD and CHD [7,14]. Variations might be a result of differences in the design of the studies, including the definition of incident cases and SES.…”
Section: Discussionmentioning
confidence: 99%
“…The endpoints were identified through linkage of the 10-digit personal identification number of each Swedish citizen with four registers: the Swedish Hospital Discharge Register, Swedish Coronary Angiography and Angioplasty Registry (SCAAR), the Stroke Register of Malmö and the Swedish Cause of Death Register. The registers have been previously described and validated for classification of outcomes [18][21]. Follow-up for the study extended to June 30, 2009.…”
Section: Methodsmentioning
confidence: 99%